2013
DOI: 10.1016/j.cub.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamin Assembly Strategies and Adaptor Proteins in Mitochondrial Fission

Abstract: Mitochondrial fission is mediated by a dynamin-related GTPase that assembles at constricted sites on the organelle. The mechanism of this GTPase in fission is related to that of classical dynamin, which severs the necks of clathrin-coated pits at the plasma membrane. Although the scale of these membrane remodeling events differs by an order of magnitude, structural studies reveal variations in the assembly properties of classical and mitochondrial dynamins that accommodate these differences. Despite this progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 88 publications
1
88
0
Order By: Relevance
“…Glu (7,39,40). In GST pull-down experiments, the Fis1 cytosolic domain tagged with GST (Fis1⌬TM-GST) bound well to yeast-expressed MBP-Mdv1 (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Glu (7,39,40). In GST pull-down experiments, the Fis1 cytosolic domain tagged with GST (Fis1⌬TM-GST) bound well to yeast-expressed MBP-Mdv1 (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Our findings may help resolve discrepancies between the roles of yeast and mammalian Fis1 in fission (7). In sequential models, Mdv1 acts as an obligate adaptor between Fis1 and Dnm1, but no mammalian Mdv1 ortholog has been identified, suggesting that mammalian and yeast fission mechanisms are divergent.…”
Section: Volume 291 • Number 39 • September 23 2016mentioning
confidence: 89%
See 2 more Smart Citations
“…The VD has recently been shown to act as a negative regulator of Drp1 self-assembly (14) with an inherent ability to interact with cardiolipin (CL) present in mitochondrial membranes (21,(23)(24)(25). Studies in yeast have shown that the VD is required for interactions with a mitochondrial adaptor protein (26), but the partner protein identified in that study is not conserved in higher eukaryotes, which suggests that the role of the VD may have evolved in higher organisms to accommodate different regulatory interactions in the cytosol and at the surface of mitochondria.…”
mentioning
confidence: 99%